The Grain of the Real within the Identity: Зрното на реалното во идентитетот - Kolozova, Katerina; Dimiškovska, Ana (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Katerina Kolozova | Катерина Колозова Title (English): The Grain of the Real within the Identity Title (Macedonian): Зрното на реалното во идентитетот Translated by (English to Macedonian): Ana Dimiškovska | Ана Димишковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 9-27 Page Count: 18 Citation (English): Katerina Kolozova, “The Grain of the Real within the Identity,” Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 9-27. Citation (Macedonian): Катерина Колозова, „Зрното на реалното во идентитетот“, превод од англиски Ана Димишковска, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): 9-27.